Coastal ecotourism development through liberty of communication and empowerment of multiethnic Bano youth - Hatmawan, Aglis Andhita; Zulham, T.; Noviar, Helmi; Triantoro, Dony Arung (Edelweiss Applied Science and Technology, 2024)
One of the key success factors of ecotourism development is collaboration with local communities. This study aims to explore the ethnographic and phenomenological communication dynamics of multiethnic Bano youth members of Forum Komunikasi Anak Bangsa (FORKAB), as well as their potential collaboration with local communities in developing sustainable ecotourism. The study employed qualitative research design, interviewing 20 informants from four regencies: Aceh Barat, Aceh Besar, Aceh Jaya, and Nagan Raya. Triangulation was employed to ensure the validity of the data. The findings suggest that there is equalitarian two-way communication that is friendly, mutually respectful, and open between members of FORKAB. Participation is voluntary and spontaneous, driven by self-initiative as well as persuasion of external motivators throughout the four phases of participation: planning, implementation, evaluation, and benefit generation. The research implications are important for policy makers and management in promoting sustainable ecotourism in the region.